Lipid-based nanocarriers for enhanced gentamicin delivery: a comparative study of liquid crystal nanoparticles and liposomes against Escherichia coli biofilms - Anam Ahsan; Timothy J. Barnes; Nicky Thomas; Santhni Subramaniam; Clive A. Prestidge (Drug Delivery and Translational Research, 2025)
Conventional antibiotic therapies often fail to eradicate bacterial biofilms due to limited penetration, altered microenvironments, and the presence of persister cells, contributing to persistent and recurrent infections. As a result,the growing threat of antibiotic-resistant bacteria, particularly those forming biofilms, underscores the urgent need for alternative therapeutic strategies. Lipid-based drug delivery systems have emerged as effective nanocarriers for antimicrobials, offering a promising strategy to combat bacterial biofilms due to their biomimetic properties, biocompatibility, and ability to navigate the complex physical, chemical, and biological barriers posed by biofilms. In this study, we compared liquid crystal nanoparticles (LCNPs) and liposomes as delivery systems for gentamicin (GEN) against Escherichia coli (E. coli ) (ATCC 25922 and ATCC 35218) in both planktonic and biofilm forms. Transmission electron microscopy analysis confirmed the particle size of GEN-loaded LCNPs (~ 200 nm) and GEN-loaded liposomes (~ 160 nm), with cubic-shaped LCNPs and lipid bilayer-structured liposomes which remained stable over three weeks at 4ºC. Loading GEN into lipid-based nanoparticles resulted in a two-fold reduction in minimum inhibitory concentration values, without significantly altering the minimum bactericidal concentration. Notably, GEN-LCNPs led to a significant fourfold (for E. coli ATCC 25922) and threefold (for E. coli ATCC 35218) reduction in inhibitory concentrations in biofilm states compared to unformulated GEN, achieving a minimum biofilm inhibitory concentration (MBIC) of 50 μg/mL and 100 μg/mL (P < 0.0001), respectively. In contrast, liposomes showed only a twofold reduction in MBIC values (100–150 μg/mL) for both bacterial biofilms. GEN-loaded LCNPs also reduced the E. coli ATCC 25922 colony-forming unit count by 5000-fold and 4000-fold, while liposomes with similar particle size did not significantly improve GEN’s antimicrobial activity. Moreover, LCNPs improved GEN efficacy regardless of particle size or Pluronic ® concentration. In conclusion, our findings suggest that GEN-loaded LCNPs demonstrated superior antimicrobial efficacy against E. coli biofilms compared to liposomes, highlighting their potential as effective nanocarriers for combating antibiotic-resistant infections. Graphical Abstract

Monitoring river flow status using low-cost wildlife camera and image segmentation artificial intelligence - Jie Bao; Yunxiang Chen; Lupita Renteria; Morgan Barnes; Brieanne Forbes; Sophia McKever; Amy Goldman; Timothy Scheibe; James Stegen (Environmental Modelling & Software, 2025)

Supplemental Feeding as a Driver of Population Expansion and Morphological Change in Anna's Hummingbirds - Nicolas M. Alexandre; Faye G. Romero; Simon G. English; Eliza Grames; Felipe Garzón‐Agudelo; Kevin Epperly; Timothy Barnes; Donald R. Powers; Audrey E. Smith; Zoë Migicovsky; Laura Stein; Saron Akalu; et al. (Global Change Biology, 2025)
Bird beaks are highly adaptable, with the potential to undergo rapid morphological shifts in response to environmental change such as climatic variation or food availability. Anna's Hummingbirds ( Calypte anna ) have undergone dramatic population range expansions over the last 160 years into novel climatic regimes, where supplemental feeders and introduced plant species are frequented. We used museum specimens to measure and characterize the shape of Anna's Hummingbird bills, hypothesizing that the introduction of novel food sources and the colonization of colder climates were associated with distinct dimensions of beak morphology. We estimated feeder and Eucalyptus availability using data from archived newspaper databases and found that these two abundances are linked to population increases in Anna's Hummingbirds, while feeders were associated with changes to beak morphology. We found that bill size and shape changed with feeder use, exhibiting a more tapered and longer bill and a distinct maxillary constriction. In males, dorsal bill shape increased in pointedness, which may have provided an advantage with increased agonistic encounters at feeders. In contrast, bill size decreased in association with lower temperatures at higher latitudes. Our data document rapid morphological changes in the Anna's Hummingbird's bill induced by human‐caused environmental changes over the last century.

Molecular shifts in dissolved organic matter along a burn severity continuum for common land cover types in the Pacific Northwest, USA - J. Alan Roebuck; Samantha Grieger; Morgan E. Barnes; Xia Gillespie; Kevin D. Bladon; John D. Bailey; Emily B. Graham; Rosalie Chu; William Kew; Timothy D. Scheibe; Allison N. Myers-Pigg (Science of The Total Environment, 2025)

ACPSEM position paper: recommendations for a digital general X-ray quality assurance program - Timothy Ireland; Amanda Perdomo; Kam L. Lee; Adam Jones; Peter Barnes; Thomas Greig; Susan E. Reynolds (Physical and Engineering Sciences in Medicine, 2024)
This guideline has been prepared by the ACPSEM to provide a standardised quality assurance program to be used within General X-ray imaging environments. The guideline includes the responsibilities of various multidisciplinary team members within medical imaging facilities. It must be noted that the listed tests and testing frequencies are not intended to replace or become regulatory requirements. Implementing a quality assurance program as outlined in this position paper is there to ensure best practice for imaging facilities by providing a framework to establish and monitor correct equipment performance. The current document has been produced through an extensive review of current international practices and local experience within the Australasian healthcare environment. Due to the constant evolution of digital radiographic equipment, there is no current consensus in international quality assurance guidelines as they continue to be adapted and updated. This document describes the current state of the use of digital General X-ray equipment in the Australasian environment and provides recommendations of test procedures that may be best suited for the current medical imaging climate in Australasia. Due to the everchanging developments in the medical imaging environment and the ability of new technologies to perform more complex tasks it is believed that in the future this document will be further reviewed in the hopes of producing a more globally agreed upon standard quality assurance program. Any such adjustments that are deemed to be necessary to Version 1.0 of this document will be provided in electronic format on the ACPSEM website with a notification to all parties involved in the use of digital General X-ray equipment. This guideline does not provide detailed methodologies for all the quality control tests recommended as it is it is expected that the professionals implementing aspects of this quality assurance program have the working knowledge and access to appropriate resources to develop testing methodologies appropriate for their local imaging environment.

Bioenergetic mapping of ‘healthy microbiomes’ via compound processing potential imprinted in gut and soil metagenomes - Craig Liddicoat; Robert A. Edwards; Michael Roach; Jake M. Robinson; Kiri Joy Wallace; Andrew D. Barnes; Joel Brame; Anna Heintz-Buschart; Timothy R. Cavagnaro; Elizabeth A. Dinsdale; Michael P. Doane; Nico Eisenhauer; et al. (Science of The Total Environment, 2024)

New pathways for women’s empowerment in pastoralist Maasai households, Tanzania - Timothy D. Baird; Emily Woodhouse; J. Terrence McCabe; Paul Barnes; Felista Terta; Naomi Runda (Journal of Rural Studies, 2024)

Environmental plastics in the context of UV radiation, climate change, and the Montreal Protocol - Marcel A. K. Jansen; Anthony L. Andrady; Paul W. Barnes; Rosa Busquets; Laura E. Revell; Janet F. Bornman; Pieter J. Aucamp; Alkiviadis F. Bais; Anastazia T. Banaszak; Germar H. Bernhard; Laura S. Bruckman; Donat‐P. Häder; et al. (Global Change Biology, 2024)

White spot syndrome virus in Alabama red swamp crayfish ( Procambarus clarkii ) - Timothy J. Bruce; Jason W. Abernathy; Nicole Tripp; Nicholas Barnes; Courtney E. Harrison; Abdulmalik A. Oladipupo; Justin D. Krol; Allison L. Wise; Janet V. Warg; James A. Stoeckel (Journal of Fish Diseases, 2024)

Multiple lines of evidence to assess risk from dioxins and dioxin-like chemicals in sediment and fish from waterbodies along a large prairie river - Markus Brinkmann; Stephanie Petersen; Alexander Pelletier; Leland Bryshun; Nicole Schaefer; Michaella Barnes; Lorne Doig; Graham Strickert; Timothy Jardine (Journal of Soils and Sediments, 2024)

Research priorities for the sustainability of coral-rich western Pacific seascapes - Graeme S. Cumming; Maja Adamska; Michele L. Barnes; Jon Barnett; David R. Bellwood; Joshua E. Cinner; Philippa J. Cohen; Jennifer M. Donelson; Katharina Fabricius; R. Quentin Grafton; Alana Grech; Georgina G. Gurney; et al. (Regional Environmental Change, 2023)
Nearly a billion people depend on tropical seascapes. The need to ensure sustainable use of these vital areas is recognised, as one of 17 policy commitments made by world leaders, in Sustainable Development Goal (SDG) 14 (‘Life below Water’) of the United Nations. SDG 14 seeks to secure marine sustainability by 2030. In a time of increasing social-ecological unpredictability and risk, scientists and policymakers working towards SDG 14 in the Asia–Pacific region need to know: (1) How are seascapes changing? (2) What can global society do about these changes? and (3) How can science and society together achieve sustainable seascape futures? Through a horizon scan, we identified nine emerging research priorities that clarify potential research contributions to marine sustainability in locations with high coral reef abundance. They include research on seascape geological and biological evolution and adaptation; elucidating drivers and mechanisms of change; understanding how seascape functions and services are produced, and how people depend on them; costs, benefits, and trade-offs to people in changing seascapes; improving seascape technologies and practices; learning to govern and manage seascapes for all; sustainable use, justice, and human well-being; bridging communities and epistemologies for innovative, equitable, and scale-crossing solutions; and informing resilient seascape futures through modelling and synthesis. Researchers can contribute to the sustainability of tropical seascapes by co-developing transdisciplinary understandings of people and ecosystems, emphasising the importance of equity and justice, and improving knowledge of key cross-scale and cross-level processes, feedbacks, and thresholds.

Approximation of hindered zonal settling rates for flocculated inorganic/organic composite suspensions in inertial flow conditions - Alexander P.G. Lockwood; Jacob R.L. Rumney; Martyn G. Barnes; Jonathan M. Dodds; Jeffrey Peakall; Timothy N. Hunter (Journal of Water Process Engineering, 2023)

Stable chlorine isotope behavior during volcanic degassing of H2O and CO2 at Mono Craters, CA - Jaime D. Barnes; Timothy J. Prather; Miguel Cisneros; Kenneth Befus; James E. Gardner; Toti E. Larson (Bulletin of Volcanology, 2014)

Representation of motion onset and offset in an augmented Barlow-Levick model of motion detection - Timothy Barnes; Ennio Mingolla (Journal of Computational Neuroscience, 2012)

Assessment of regional and local biodiversity in tropical and subtropical coastal habitats in the East African Marine Ecoregion - Natalie Barnes; Roger N. Bamber; Graham Bennell; Nils Cornelius; David Glassom; Sophie Conroy-Dalton Henderson; Narriman Jiddawi; Christine N. W. Lee; Adriano Macia; Daudi J. Msangameno; José Paula; Saleh Yahya; et al. (Biodiversity and Conservation, 2011)